Study On Piping Stresses At Gas District Cooling (GDC) Universiti Teknologi Petronas (UTP) Plant - Izhar Adli Bin Mohd Arif, Izhar Adli Bin Mohd Arif (Universiti Teknologi Petronas, 2009)
Stresses in piping system have been a major concern in designing a plant because pipes are the main transportation medium for many processes. Stresses are found in pipes where failure to these pipes can cause severe problem due to their criticality. This study was aimed to investigate the types of piping system in GDC UTP plant, identify and analyze which system having critical stresses and also find ways to rectify them. To date, there was no study conducted to check the stresses on the critical piping system of the plant. The scope of study was to determine the stresses in piping systems and to suggest ways to rectify them. The study was performed by identifying the critical piping system based on the characteristics and specifications of the piping system using the plant design data. Analyses were conducted by modelling the pipe using stress analysis software, CAESAR II 5.0, to check the types and also the value of the stresses exerted. The values were then compared for conformance with the governing codes. From the analyses done, piping systems in GDC UTP plant were categorized into four (4) groups according to the fluid they were carrying; namely natural gas (primary fuel), diesel (secondary fuel), chilled water and instrument air piping systems. The study concluded that only chilled water piping system was considered critical. In the analyses done on the chilled water piping system, it was found that the axial stress, hoop stress and torsion stress on the pipe were well below the allowable stresses as govern by ASME B31.1. However, the bending stress was found to be over the maximum allowable design limit. To rectify the excessive bending stress problem, it was recommended that modification could be done with the number of supports along the pipe. Analyses done on the recommended modification showed that it could reduce the maximum bending stress along the pipe.